IN SILICO ANALYSIS OF ANTIFUNGAL POTENTIAL OF Centella asiatica ACTIVE COMPOUNDS AS NATURAL BIOFUNGICIDES FOR OIL PALM FUNGAL DISEASE CONTROL: ANALISIS IN SILICO POTENSI ANTIFUNGI SENYAWA AKTIF Centella asiatica SEBAGAI BIOFUNGISIDA ALAMI UNTUK PENGENDALIAN PENYAKIT JAMUR PADA TANAMAN KELAPA SAWIT - Danie Indra Yama; Muhammad Fiqri Marwanto; Adinda Aurelia Putri; Delia Ramadani; I Komang Wahyu Pradita; Muhammad Hidayat; Deko; Bahij Islami Pasha; Dodi Iskandar (ROCE : Jurnal Pertanian Terapan, 2026)
This study aimed to analyze the potential of active compounds in pegagan (Centella asiatica) as natural antifungal agents using an in silico approach with PASS Online, SwissADME, and pkCSM. The PASS Online analysis showed that most active compounds of pegagan had antifungal activity probability (Pa) values above 0.5, indicating relatively high biological potential. The compounds with the highest activity were 3-O-beta-D-Glucopyranosyl sitosterol (0.722), Centellin (0.715), Centellicin (0.655), Asiatic acid (0.651), and Kaempferol (0.651). Triterpenoid, flavonoid, and sesquiterpene compounds are known to act through mechanisms including disruption of the fungal cell membrane, inhibition of cell wall synthesis, interference with energy metabolism, and enhancement of oxidative stress in pathogenic cells. SwissADME analysis indicated that the majority of compounds exhibited good solubility, moderate lipophilicity, and bioavailability scores consistent with biological activity. Acetylursolic acid showed the highest bioavailability score of 0.85, while most other compounds ranged between 0.55 and 0.56. The drug-likeness results demonstrated that most compounds complied with Lipinski, Veber, and Muegge rules, indicating their potential as bioactive antifungal candidates. Physicochemical property analysis revealed TPSA values, hydrogen-bond donors and acceptors, and molecular flexibility that support membrane penetration and interactions with fungal biological targets. In addition, pkCSM results showed that most compounds were non-mutagenic, non-hepatotoxic, and exhibited relatively low environmental toxicity. Overall, the results suggest that pegagan has strong potential as a source of environmentally friendly natural antifungal compounds and may be further developed as a biofungicide for controlling fungal diseases in oil palm plants.